Is China Taking the Lead in AI? - Ding, Jeffrey; Ding, Jeffrey; Klotz, Frieda (MIT Sloan Management Review, 2020)
Although some observers have compared the rivalry between the United States and China over AI to the Cold War, Oxford researcher Jeffrey Ding says the analogy is flawed. AI is a general-purpose technology that can be applied across many different domains - including natural language processing, computer vision, and predictive analytics - and claiming that China has an edge ignores some important structural advantages for the U.S.